Effects of carbohydrate content in seeds on the germination and viability after cryopreservation - Arystan, L.B.; Kamsayeva, T.Kh.; Tleukenova, S.U.; Sirman, D.Yu.; Nurkenova, A.T. (Fundamental and Experimental Biology, 2021)
This article is devoted to the study of the influence of cryopreservation on the preservation of sowing qualities of seeds of representatives of the genus Picea: P. asperata(Rough spruce) and P. pungens (Spiny spruce). As an alternative shock method of cryopreservation, the method of step-by-step 3-step temperature reduction was used 1 stage +4 °C, 2 stage –18 °C, 3 stage –196 °C liquid nitrogen. Additionally, the effect of 4 time intervals (1 hour, 24 hours, 72 hours and 168 hours) of step freezing on seed quality was investigated. To explain the results by photometry, the total carbohydrate content of the seeds is determined before the 3rd freezing step (cryo interaction). The analysis of the results of germination showed that the seeds of the stud-ied species respond in different directions to the step cryo freezing. So, seeds of P. asperata germination in all tree experimental variants are higher on 4–32 % than in the control variant; and the maximum results are revealed in the variant with time intervals of 168 hours. For P. pungensseeds, the germination rates in experimental variants were on 18–22 % lower than in the control; and the largest germination rate of seeds among experimental variations are revealed in variant with interval 24 hours. The determination of the total carbohy-drate content of the tested seeds at different cryogenic freezing intervals found that this indicator varied significantly depending on the time interval. The lowest values of total carbohydrates are found in variation with a time interval — 24 hours. The maximum total carbohydrate content is determined in a variation with a time interval — 1 hour. Correlation analysis between seed germination indices and total carbohydrate content established a high relationship between these indices. So, for P. asperata, the value of the Pearson coefficient was 0.86, and for P. pungensseeds — 0.91.